L.A. confidential [videorecording (Blu-Ray)] - Hanson, Curtis; Hanson, Curtis; Hanson, Curtis; Spacey, Kevin; Basinger, Kim, 1953-; Crowe, Russell, 1964-; Pearce, Guy, 1967-; Ellroy, James, 1948- (Twentieth Century Fox Home Entertainment, 2015)
Three detectives each use their own approach to find the truth behind a group of murders.